Project title: an exploration of high school learners’ educational journey and how it shapes their aspirations - Malhotra, Vidushi (Department of Social Development, 2019)
As a consequence of Apartheid, schools today are still grappling with the process of desegregation of an unequal education system in South Africa. The inequality of skills acquired by children and the poor quality of education received undermines their ability to understand or develop aspirations. This qualitative study aims to explore the educational journey of high school learners and how the journey shapes their aspirations. Drawing upon the background of high school learners, particularly their family background, socio-economic status and neighborhood, this study examines the aspirations informed by the educational journey of learners. First, the findings revealed that academic interests of learners were not steered by the stature of the school they attended. The reasons that are understood to be positively affecting the change in academic interests are more self-driven than influenced by factors that are outside of the personal journey of the learners. Second, parents who were educated themselves valued the importance of quality education, which meant not only improving marks, but also building and working towards an aspiration. Third, learners who came from decent and peaceful neighborhoods mostly reported a supportive community and one that is always striving for a better future through education. This community dynamic also had a positive effect on the learners’ focus and ability to study after school hours. The results of the study also mention the shortcomings of the current South African education system in the way that it only allows for limited real-world exposure and restricts learners from making informed subject choices. Recommendations for corrective measures in the form of introduction of gap year programs, better subject choices and exposure to career fairs and interaction with field experts are made by the researcher.